The Challenge by Multiple Environmental and Biological Factors Induce Inflammation in Aging: Their Role in the Promotion of Chronic Disease - Bachmann, María Consuelo; Bellalta, Sofía; Basoalto, Roque; Gómez-Valenzuela, Fernán; Jalil, Yorschua; Lépez, Macarena; Matamoros, Anibal; von Bernhardi, Rommy (Frontiers in Immunology, 2020)
The aging process is driven by multiple mechanisms that lead to changes in energy production, oxidative stress, homeostatic dysregulation and eventually to loss of functionality and increased disease susceptibility. Most aged individuals develop chronic low-grade inflammation, which is an important risk factor for morbidity, physical and cognitive impairment, frailty, and death. At any age, chronic inflammatory diseases are major causes of morbimortality, affecting up to 5–8% of the population of industrialized countries. Several environmental factors can play an important role for modifying the inflammatory state. Genetics accounts for only a small fraction of chronic-inflammatory diseases, whereas environmental factors appear to participate, either with a causative or a promotional role in 50% to 75% of patients. Several of those changes depend on epigenetic changes that will further modify the individual response to additional stimuli. The interaction between inflammation and the environment offers important insights on aging and health. These conditions, often depending on the individual’s sex, appear to lead to decreased longevity and physical and cognitive decline. In addition to biological factors, the environment is also involved in the generation of psychological and social context leading to stress. Poor psychological environments and other sources of stress also result in increased inflammation. However, the mechanisms underlying the role of environmental and psychosocial factors and nutrition on the regulation of inflammation, and how the response elicited for those factors interact among them, are poorly understood. Whereas certain deleterious environmental factors result in the generation of oxidative stress driven by an increased production of reactive oxygen and nitrogen species, endoplasmic reticulum stress, and inflammation, other factors, including nutrition (polyunsaturated fatty acids) and behavioral factors (exercise) confer protection against inflammation, oxidative and endoplasmic reticulum stress, and thus ameliorate their deleterious effect. Here, we discuss processes and mechanisms of inflammation associated with environmental factors and behavior, their links to sex and gender, and their overall impact on aging.